2017
DOI: 10.1111/ijd.13540
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological aspects of cutaneous erythematous‐papular eruptions induced by immune checkpoint inhibitors for the treatment of metastatic melanoma

Abstract: Our study showed the clinical features of a group of melanoma patients with CMPE for ICBT and emphasized the wide spectrum of histological findings as well as their immunohistochemical profile. Differential diagnosis can be difficult with CMPE provoked by other therapies as was seen in our comparison group of anti-BRAF-induced eruptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Dysregulation of immune tolerance due to ICIs results in unbridled T-cell infiltration leading to keratinocyte injury [20]. A varying degree of infiltration by eosinophils [21] and peripheral eosinophilia [22,23] has also been previously described.…”
Section: Histopathologymentioning
confidence: 90%
“…Dysregulation of immune tolerance due to ICIs results in unbridled T-cell infiltration leading to keratinocyte injury [20]. A varying degree of infiltration by eosinophils [21] and peripheral eosinophilia [22,23] has also been previously described.…”
Section: Histopathologymentioning
confidence: 90%
“…A summary of the suprabasal acantholytic dermatologic toxicities associated CPIs reported in the literature (including the two patients in this report) is presented in Table . Overall, 13 patients (including the two in this report) with a median age of 64 years (range: 51‐75 years) developed suprabasal acantholytic dermatologic toxicities (Grover‐like, n = 8; “lichenoid dermatitis with suprabasal acantholysis/intraepithelial vesicle”, n = 4; PNP‐like, n = 1) associated with CPIs (ipilimumab = 4; nivolumab = 2; pembrolizumab = 2; combined CPIs = 5).…”
Section: Discussionmentioning
confidence: 92%
“…A systematic review of extensive GD found recent transplant in 20% of cases, and individual reports have found cases following bone marrow, renal, liver, and heart transplants . Reports of eruptions following initiation of drugs are numerous and include, but are not limited to, sulfadoxine‐pyrimethamine, recombinant IL‐4, BRAF inhibitors, ipilimumab, and other immune checkpoint inhibitors …”
Section: Review Of Etiopathogenesis Of Grover Diseasementioning
confidence: 99%
“…Although several drugs have been associated with the onset of GD, the benefit of these medications often outweighs the risks of discontinuing them. Therefore, in these cases, the inciting drug is usually continued and combined with symptomatic treatment of GD …”
Section: Preventionmentioning
confidence: 99%